PEMBUATAN PEMANAS INDUCTION UNTUK SISTENSIS MATERIAL DENGAN MOTODA HIDROTERMAL - Nurkholis, Nurkholis; Bawono, Ari; Priyono, Priyono (BERKALA FISIKA, 2020)
Induction heaters furnace could work faster and more efficiently compared to the conventional electric heaters, but a temperature regulation system should be quite good and stable with a fairly long operating time. This method is suitable for the synthesis of materials that require a long operation time, such as hydrothermal process. This study aims to design and evaluate the induction heater using K-type thermocouple sensor with proportional Integral Derivative (PID) control system. Thermocouple sensors calibration tested on a set point of 150 °C to 350 °C gives a good result at stable temperature values after tested less than 90 seconds and have low error rates at 0,02% - 0,16%.  Hydrothermal synthesis process on reactor with a heating temperature of 300 °C for 24 hours gives a good result.